A tale of two cities: implications of the similarities and differences in collaborative approaches within the digital libraries and digital humanities communities. - Siemens, Lynne; Cunningham, Richard; Duff, Wendy; Warwick, Claire (Literary & Linguistic Computing, 2011)
In addition to drawing upon content experts, librarians, archivists, developers, programmers, managers, and others, many emerging digital projects also pull in disciplinary expertise from areas that do not typically work in team environments. To be effective, these teams must find processes—some of which are counter to natural individually oriented work habits—which support the larger goals and group-oriented work of these digital projects. This article will explore the similarities and differences in approaches within and between members of the Digital Libraries (DL) and Digital Humanities (DH) communities by formally documenting the nature of collaboration in these teams. While there are many similarities in approaches between DL and DH project teams, some interesting differences exist and may influence the effectiveness of a digital project team with membership that draws from these two communities. Conclusions are focused on supporting strong team processes with recommendations for documentation, communication, training, and the development of team skills and perspectives.